Parents' Perspectives on Diagnosis and Decision-Making regarding Ventilator Support in Children with SMA Type 1 - Pechmann, Astrid; Langer, Thorsten; Kirschner, Janbernd (Neuropediatrics, 2022)
Spinal muscular atrophy (SMA) is a rare neuromuscular disorder with a broad clinical spectrum. The most severe phenotype—SMA type 1—is characterized by marked muscle weakness also affecting bulbar and respiratory function. Life expectancy of children with SMA type 1 is expected to be less than 2 years without ventilator support or disease-specific drug treatment. The aim of this study was to evaluate parents' perspectives on the process of decision-making regarding ventilator support in children with SMA type 1. Fourteen semi-structured interviews were performed with parents of children with SMA type 1 that decided either for or against ventilator support for their child. All children were diagnosed prior to the approval of SMA-specific drug treatment. Interviews were recorded and transcribed verbatim. Data analysis was performed using a qualitative content analysis approach according to Mayring. Parents experienced that they were not adequately informed about the disease and treatment options in first informed consent discussions. Especially regarding ventilator support, parents perceived that they were not offered ventilator support as an actual option for treatment. Regarding the decision of whether or not to offer ventilator support, parents reported that their attitude toward ventilator support and contact with other affected families or patient advocacy groups were more likely to influence the decision than the content of informed consent discussions with physicians. Our results underline the importance of an interdisciplinary team not only to provide parents with relevant information but also to consider the criteria of a patient-centered medicine.
Keywords: spinal muscular atrophy; ventilator support; decision-making; caregiver